Odpowiedzi

2010-02-08T21:31:24+01:00
A) x - 3y = 5 | * (-4)
4x + 5y = 1

-4x - (-12y) = -20
4x + 5y = 1

17y=-19 /:17
y=-19/17
4x + 5y = 1
4x + (-19/17) = 1
4x = 1i19/17 /4
x = 1i19/17 na 4
y= -19/17

b) 3y = 6x + 12
7x = 5y

3y = 6x + 12 /*5
-5y = -7x /*3

15y = 30x + 60
-15y = -21x
0=9x+60
-60=9x /9
6,(6)=x

3y=6x+12
3y=6*6,(6)+12
3y=39,6+12
3y=51,6 /:3
y=17,2
x=6,6
1 5 1
2010-02-08T21:33:27+01:00
A) x - 3y = 5 | * (-4)
4x + 5y = 1

-4x+12y=-20
4x+5y=1

17y=-19/:17
y=19/17

4x+5y=1
4x=109/19 /:4
x=109/76


b) 3y = 6x + 12
7x = 5y/:7

3y=6x+12
x=5/7

3y=84/7 /:3
y=4

2 3 2